Effect of non-genetic factors on replacement rate and its components in Murrah buffaloes of Tamil Nadu - THIRUVENKADAN, A K; DEVENDRAN, P (The Indian Journal of Animal Sciences, 2014)
The average value (in %) for abnormal birth, male birth, female birth, death of female calves, culling of female calves, replacement rate on basis of total pregnancies and total female calves born were 2.82, 51.4, 48.6, 38.8, 21.2, 19.4 and 40.0 respectively. On an average 4 to 5 pregnancies were required for one female calf to reach milking herd. Among the non-genetic factors, period of birth contributed for major variation in replacement rate and its components. The effects of different non-genetic factors (viz. season, periods and parity) affecting replacement rate and its components revealed that period of birth affected the replacement rate and its components highly significantly (P<0.01). Beyond fifth lactation the efficacy of cows to replace a heifer decreased gradually.